2015
DOI: 10.7314/apjcp.2014.15.24.10565
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer in Asian American Populations: a Neglected Health Disparity

Abstract: Gastric cancer incidence rates vary dramatically by world region with East Asia having the highest rate. The Asian population of the United States (US) is growing rapidly and over 17 million Americans are of Asian descent. A majority of Chinese, Korean and Vietnamese Americans are immigrants. Americans of East and Southeast Asian descent experience marked gastric cancer disparities and the incidence rate among Korean men in the US is over five times higher than the incidence rate among non-Hispanic white men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…AANHPIs are more likely than NHWs to be diagnosed with stomach cancer at a localized or regional stage (Fig. ), possibly because of awareness of the higher risk of stomach cancer among Asian Americans and/or screening recommendations by some medical societies . The American Society for Gastrointestinal Endoscopy states that endoscopic screening may be considered for first‐generation immigrants aged 40 years or older from high‐risk Asian countries such as Japan or China, especially if there is a history of gastric cancer in a first‐degree relative .…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…AANHPIs are more likely than NHWs to be diagnosed with stomach cancer at a localized or regional stage (Fig. ), possibly because of awareness of the higher risk of stomach cancer among Asian Americans and/or screening recommendations by some medical societies . The American Society for Gastrointestinal Endoscopy states that endoscopic screening may be considered for first‐generation immigrants aged 40 years or older from high‐risk Asian countries such as Japan or China, especially if there is a history of gastric cancer in a first‐degree relative .…”
Section: Selected Findingsmentioning
confidence: 99%
“…4), possibly because of awareness of the higher risk of stomach cancer among Asian Americans and/or screening recommendations by some medical societies. 68 The American Society for Gastrointestinal Endoscopy states that endoscopic screening may be considered for firstgeneration immigrants aged 40 years or older from high-risk Asian countries such as Japan or China, especially if there is a history of gastric cancer in a first-degree relative. 69 Likely because of the earlier stage at diagnosis, AANHPIs have higher 5-year survival than NHWs, 40% versus 28% in males and 38% versus 34% in females, respectively ( Fig.…”
Section: Cancer Sites With Higher Rates For Aanhpismentioning
confidence: 99%
“…The incidence is especially high in Japan as compared to other countries [241]. Therefore, risk factors for gastric cancer and its association with GT or GTE have been investigated in six cohort studies from Japan [242][243][244][245][246][247], but no similar cohort study was published from other countries ( Table 9).…”
Section: Gastric Cancermentioning
confidence: 99%
“…With one exception [254] published 11 years earlier, all case control studies were performed in China (Table 9); some Chinese areas also have a high gastric cancer incidence, but still lower than in Japan [241]. The results from these studies are ambiguous at best: the Japanese study found a decrease with high GT intake (set at >10 cups GT/day) [254]; two Chinese studies [230,237,238] found a similar protection with "high GT intake", which here was set at >250 g tea/month.…”
Section: Gastric Cancer-epidemiological Evidencementioning
confidence: 99%
“…In particular, even in low prevalence countries, health care providers should consider screening with primary prevention, including endoscopy for high-risk populations such as Asian immigrants. 56 To overcome these limitations, several state-of-the art technologies are now under development. Multitarget stool DNA testing could be considered as a noninvasive alternative in gastric cancer screening, as recently reported for colorectal cancer.…”
Section: Westmentioning
confidence: 99%